Revising the Trade and Economic Relations of Right – Bank Ukraine and west Ukrainian Lands with Poland in the Latter Half of the 16 th by the Close of 18 th Century. (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The situation concerning the trade and economic relations of the Ukrainian lands with Poland in the latter half of the 16 th by the close of 18th century is examined in this article as well as the transport of goods by river routs or by lands to the Polish market resulting in the establishment of the largest business centers is given. Both social and property status of merchantmen and marketers ( feudal lords, handicraft workers, bourgeoisies, peasants, etc. ), and assortment of goods. Any merchant profit is analyzed and the profit margin is fixed as well. Differences in getting profits by the Ukrainian merchantmen in comparison with West European are shown.